PENDAPATAN MASYARAKAT DARI HASIL HUTAN BUKAN KAYU DISEKITAR KAWASAN CAGAR ALAM RAYA PASI KELURAHAN NYARUMKOP KECAMATAN SINGKAWANG TIMUR - Karyon, Epifania Yulie; Roslinda, Emi; Riyono, Joko Nugroho (Universitas Tanjungpura, 2016)
The public revenue which isÂ living around the forests depend on forest products. Non timber forest products can be a source of public revenue. The purpose of this study was to determine the type of timber forest products are utilized by people around the nature reserve of area Raya Pasi, the income received by the public and the factors related to people's income. This study uses a survey by interview with a guide questionnaire. Sampling was done by purposive sampling with the number of respondents are 70 households Analysis conducted by descriptive and inferential. The results showed that timber forest products are utilized by people. Fruits, vegetables and medicinal plants. The average income they earned around the nature reserve area Raya Pasi average of Rp. 11.995 million / household / year. Factors related to the type of revenue is the amount collected, while the number of working members and the number of hours worked to collect non-timber products do not have a significant relationship. The numbers of non forest products are collected was the factor have related by peopleâ€™s income. Keywords: Public revenue, non-timber forest products, Nature Reserve Raya Pasi